Reviewing Bioinspired Technologies for Future Trends: A Complex Systems Point of View - Arena, Paolo; Bucolo, Maide; Buscarino, Arturo; Fortuna, Luigi; Frasca, Mattia (Frontiers in Physics, 2021)
In this contribution, the main guidelines that, in the opinion of the authors, will address bioinspired technologies in the next future are discussed. The topics are related to some specific subjects. Indeed the presented perspectives could be really useful to remark how bioinspired technologies can be applied to solve every day problems in a low cost and sustainable way. Moreover, all the considerations reported hallmark the need of bioinspired systems to change design paradigm main concept that bioinspired systems need a change of design paradigm. Efficient and alternative bioinspired systems cannot be designed by only looking at macroscopic scale as observed in nature. The efforts of this paper are oriented towards providing a wide perspective on bioinspired technologies as complex systems where nonlinear phenomena are fundamental elements.